Short term outcome of distal (ventricular) His bundle pacing and atrioventricular node ablation in patients with symptomatic atrial fibrillation - Refining the concept. (19th May 2022) - Man, S; Vali, Z; Ebeid, A; Abouelmagd, K; Dhutia, H; Somani, R; Ng, G A; Ibrahim, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Many patients with atrial fibrillation (AF) do not benefit from rhythm control due to failed catheter ablation, advanced left atrial disease and comorbidities. "Pace and AV node (AVN) ablation" strategy is often adopted for rate control but with a substantial risk of pacing-induced cardiomyopathy. His bundle pacing (HBP) enables physiological biventricular activation through the His Purkinje conduction system. However, the proximity of the HBP lead to the site of AV node ablation may potentially compromise lead integrity in patients who undergo conventional HBP and AVN ablation. Therefore, we have modified HBP by placing the HBP lead distally at the ventricular side of the His bundle (D-HBP) before AVN ablation in patients with symptomatic AF. All patients had a backup RV lead. Method: Patients who had D-HBP as part of a "Pace and AVN ablation" strategy were retrospectively analysed. Implant and device clinic follow-up data were collected and analysed. Result: Twenty-one patients who had "pace and AVN ablation strategy" with D-HBP between 26th February 2020 and 3rd November 2021 were included. They had a mean age of 75 ± 1.4 years (mean ± SEM), NYHA class of 2.1 ± 0.2, QRS duration of 106 ± 5.3ms and 50% had at least moderately impaired LV systolic function. Seventeen patients (81%) had narrow QRS duration. D-HBP was successful in twenty of twenty-one patients (95%). At D-HBP implant, the mean acute threshold of the HBP lead was 0.96 ± 0.12V at 0.5 ± 0.05ms and the mean HBP lead impedance was 548.1 ± 29.5Ω. Selective HBP pacing was observed in thirteen of twenty patients. The mean QRS duration of HBP paced beats was 104.5 ± 4.7ms. Failure to capture the His bundle was observed in one patient. AVN ablation was performed on the same day after D-HBP in eleven patients and as a subsequent procedure in nine patients. The mean duration of procedure and fluoroscopy for D-HBP were 77.4 ± 4.6 minutes and 11.9 ± 1.4 minutes respectively. There were no acute procedural complications with no lead damage, displacement or lead perforation observed. The median follow-up period was 207 days. The mean D-HBP lead threshold following AVN ablation was 1.1 ± 0.2 V at 0.6 ± 0.07 ms and the mean lead impedance was 433.8 ± 20.7Ω, which were similar to before AVN ablation. One patient was reprogrammed with RV pacing only for elevated HBP lead threshold after AVN ablation to 4.2 V at 1ms. The mean D-HBP percentage was 92.3 ± 6.6% and the mean estimated battery longevity of the pacemaker was 7.9 ± 0.6 years at the last follow up. There was improvement in heart failure symptoms in eight patients from previously symptomatic to NYHA class I following D-HBP and AVN ablation. Conclusion: D-HBP appear to be safe with potentially more favourable lead parameters than conventional proximal HBP in patients with symptomatic AF offered "Pace and AVN ablation" strategy.